The power of short lectures to improve support for biodiversity conservation of unpopular organisms: an experiment with worms (UNED Research Journal, 2017)
Public opinion is important in obtaining support for the conservation of biodiversity, and invertebrates have a "public relations problem" because -for reasons that are both cultural and biological- they are poorly known and often unpopular. In this article I present the results of an experiment on the power of a short lecture to improve attitude towards invertebrates, using the case of velvet worms. Velvet worms are "living fossils" that have inspired a wide range of cultural expressions, probably because of the adhesive net they use to capture prey. For the experiment, a group of 141 Costa Ricans, aged 10 to 58 years old, rated their reaction to a color photograph of Epiperipatus biolleyi, a Costa Rican species of velvet worm, before and after a five-minute lecture about the natural history of the worm. Even before the treatment, most of the respondents had a correct idea of the animal's anatomy (84%); supported the use of public funds to conserve it (71%); and more than half perceived the worm in a positive way (58%). They stated that they were willing to donate a mean of US$7,00 from their own pocket for the worm's protection (six times more if they had university education); and were less likely to reject the worm if they kept pets at home. Gender, age and education did not have any effect on most variables of attitude and knowledge. Compared with the control group, the group that received the lecture had a 17% improvement in attitude. The Costa Rican educational system, focused on nature and its conservation, can explain the generally good attitude and knowledge of invertebrates found in this study; and a five-minute natural history lecture can produce a significant improvement in perception of an animal that is generally unattractive: a worm.
Keywords: attitude towards invertebrates; quantitative effect of education; conservation of biodiversity; tropical worms; Epiperipatus biolleyi.